CHI '07 Extended Abstracts on Human Factors in Computing Systems 2007
DOI: 10.1145/1240866.1240930
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tilt-based browsing on mobile devices

Abstract: A tilt-controlled photo browsing method for small mobile devices is presented. The implementation uses continuous inputs from an accelerometer, and a multimodal (visual, audio and vibrotactile) display coupled with the states of this model. The model is based on a simple physical model, with its characteristics shaped to enhance usability. We show how the dynamics of the physical model can be shaped to make the handling qualities of the mobile device fit the browsing task. We implemented the proposed algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Research into the use of tilt interaction has since been extended to a range of domains including menu navigation, text entry, mobile museum guides, photo browsing and interacting with mobile map-based applications [3,4,11]. Most existing research has focused on the use of tilt as a means of performing panning, where the tilt angles along the x and y axes are mapped onto panning speeds in the horizontal and vertical directions.…”
Section: Tilt Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the use of tilt interaction has since been extended to a range of domains including menu navigation, text entry, mobile museum guides, photo browsing and interacting with mobile map-based applications [3,4,11]. Most existing research has focused on the use of tilt as a means of performing panning, where the tilt angles along the x and y axes are mapped onto panning speeds in the horizontal and vertical directions.…”
Section: Tilt Interactionmentioning
confidence: 99%
“…Previous research has shown that users prefer to only use one hand when interacting with maps on mobile phones [2]. Keypad interaction limits the user's freedom of movement and provides little control over panning speed [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sensors are more focused on user interaction. For example, the sensing of pose to control the orientation of graphical displays (Hinckley et al, 2005), motion as input to dynamic simulations (Cho et al, 2007) and camera input to perform cursor-like navigation and selection (Rohs, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose a tilt-based photo browsing system with enhanced controllability from a tilt dynamics model [21] and a multi-context screen dynamics model. The dynamics model is designed for remedying major controllability errors in browsing photos.…”
Section: Introductionmentioning
confidence: 99%